(untitled) (Comparative Professional Pedagogy, 2022)
The article highlights some aspects of the development and implementation of bilingual education in China. Special attention is paid to the internal and external factors that have led to the need to introduce bilingual education in China. The influence of English on the formation and development of China’s language policy, as well as the dependence of the country’s economy and human resource development on the quality of bilingual education are determined. It is stressed that in the process of China’s active participation in the global economy and international cooperation, English has become very important in the country’s bilingual education. The article summarizes the studies of Chinese scholars on the interpretation of the concept of "bilingual education". They made it possible to consider it as a process of learning two languages and using these two languages as a means of learning a part or the complete educational program; using another language as a means of learning for language minorities; learning with the dominance of the native language and limited knowledge of a foreign language, etc. Based on the results of experimental studies conducted by Chinese scholars, the expediency of introducing bilingual education in primary and basic schools in large cities and developed regions of the country is confirmed. The features of the introduction of immersion educational programs in Chinese higher education institutions are considered. Controversial issues and problems that exist in bilingual education, in particular, the insufficient number of bilingual teachers, low motivation of students to learn a second language, insufficient pedagogical conditions for the introduction of bilingual education, lack of authentic teaching and learning materials, and others are considered. Particular attention is paid to the measures taken by Chinese educational institutions to improve the level of bilingual education, in particular, the implementation of an adapted model of bilingual education in Chinese higher education institutions.